PEMBUATAN BAHAN BAKAR CAMPURAN BIODIESEL, DIESEL, ETANOL DAN AIR DALAM EMULSI STABIL - Paendong, Meiga; Sangian, Hanny F.; Bobanto, Maria D. (UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT The purpose of this research is to prepare a blended fuel of biodiesel, diesel and ethanol in stable emulsion. Biodiesel which is mixed with diesel and ethanol in certain compositions was conducted manually. The first step was to prepare ethanol from fermented palm sap and then the ethanol and water were distililed using a reflux separator. The ethanol obtained was with purity 94-96%, while 97% ethanol was produced by lime absorbsion. The next step was the mixing process between ethanol, biodiesel and ethanol, biodiesel, and diesel. Ethanol was poured into a measuring flask with a volume of 7 ml and then biodiesel was added until they formed a stable emulsion solution. The ethanol and diesel were mixed and the biodiesel was added gradually while shaken slowly forming a stable emulsion. The results showed that the composition of biodiesel, ethanol, and water with 96% ethanol were 78.76, 20.42 and 0.81% (v/v), where methyl esters were obtained from palm oil using subcritical techniques. Meanwhile, biodiesel from coconut oil with the same technique, the composition of the three components was 75.13% biodiesel, 23.90% ethanol and 0.95% air. Keywords: Biodiesel, Ethanol, Diesel, Palm Tree (Arenga pinnata SP). ABSTRAKTujuan penelitian ini adalah membuat bahan bakar campuran larutan emulsi stabil dengan mencampurkan biodiesel, diesel dan etanol. Biodiesel yang dicampur dengan diesel dan etanol pada komposisi tertentu dilakukan secara manual. Tahapan yang pertama yaitu pembuatan etanol dari nira aren yang sudah terfermentasi dan kemudian dilakukan proses destilasi etanol untuk mendapat kemurnian 94-96%, sementara untuk etanol 97 % didapat dengan cara absorsi menggunakan lime. Tahapan berikutnya yaitu proses pencampuran dilakukan dengan menggunakan etanol dengan kemurnian 94%-97%. Etanol dituangkan ke dalam gelas ukur dengan volume 7 ml dan etanol konsentrasi 96% dicampur secara perlahan hingga membentuk larutan emulsi stabil. Hasil menunjukan bahwa komposisi biodiesel, etanol, dan air dengan kosentrasi etanol 96% adalah 78.76, 20.42 dan 0.81 % (v/v) yang mana methyl ester diturunkan dari minyak sawit dengan menggunakan teknik subkritis. Sementara, biodiesel dari minyak kelapa dengan teknik yang sama, komposisi ketiga komponen adalah 75.13 % biodiesel, 23.90 % etanol dan 0.95% air. Kata kunci: Biodiesel, Etanol, Diesel, Pohon Aren (Arenga pinnata SP)